The state of erythrocyte cell membrane in patients with B-cell non-Hodgkin`s lymphoma - Тимошенко, У. В. (Problems of Environmental Biotechnology, 2017)
Investigation of urea hemolysis, osmotic and peroxidative resistance of erythrocytes in patients with B-cell non-Hodgkin’s lymphoma was done. Signs of degradation and increased permeability of erythrocyte membranes to hemoglobin were revealed in patients compared with healthy individuals.